The Famine in North Korea: Humanitarian Responses in Communist Nations - Lautze, Sue (Tufts Archival Research Center, 2005)
This issues paper is intended to raise awareness and encourage debate about the current crisis in the Democratic Peopleâs Republic of Korea (DPRK). Given the level of controversy about humanitarian interventions in North Korea, Lautze, Sue has attempted to provide a framework for analyzing the complicated and unique political, military and economic factors not common to emergencies elsewhere in the world. What is presented here should not be interpreted as fully confirmed, solid fact. Indeed, no information about North Korea should be taken as such. Instead, she has sought to provide an alternative, if controversial, methodology of interpreting and monitoring famine in North Korea. This multi-dimensional approach to understanding the intricacies of todayâs crises is in line with the Centerâs overall strategy to promote more effective responses to disasters.